OPTIMALISASI SISTEM ANTRIAN SERI PADA SARANA PELAYANAN SAMSAT BERDASARKAN TINGKAT ASPIRASI (STUDI KASUS DIKANTOR SAMSAT KOTA SRAGEN) - Ardama, Johan Dwi; Dwidayati, Nur Karomah (Unnes Journal of Mathematics, 2020)
The purpose of this study is to find out (1) the series queuing system model currently applied at the SAMSAT Office of Sragen City, (2) the effectiveness of the taxpayer service process, and (3) the optimal queuing system based on the level of aspiration so as not to harm the taxpayer and also SAMSAT. From the results of the study it was found that in SAMSAT, Sragen City followed the Single Channel Multiple Phase queue system model (tendem queue or series). Details of the queue model at the registration window and payment window are [G / G / 1]: [GD / âˆž / âˆž]. This means a queue system of arrival patterns that is distributed by the General with the number of servants covering 1 officer at each of the counters. The results of the effectiveness of the queuing system in SAMSAT, Sragen City, for one day during rush hour service, namely Tuesday, August 6, 2019 with Lq = 0.2452, Ls = 0.7085, Wq = 0.7119, Ws = 1.774, W = 53.67% .